In vitro analysis of catalase and superoxide dismutase mimetic properties of blue tattoo ink. (3rd June 2022) - Homolak, Jan
Abstract: Tattoo inks are comprised of different combinations of bioactive chemicals with combined biological effects that are insufficiently explored. Tattoos have been associated with oxidative stress; however, a recent N-of-1 study suggested that blue tattoos may be associated with suppressed local skin oxidative stress. The present study aimed to explore the attributes of the blue tattoo ink (BTI) that may explain its possible effects on redox homeostasis, namely the catalase (CAT) and superoxide dismutase (SOD)-mimetic properties that have been reported for copper(II) phthalocyanine (CuPC)—the main BTI constituent. Intenze™ Persian blue (PB) BTI has been used in the experiment. CAT and SOD-mimetic properties of PB and its pigment-enriched fractions were analyzed using the carbonato-cobaltate (III) formation-derived H2 O2 dissociation and 1, 2, 3-trihydroxybenzene autoxidation rate assays utilizing simple buffers and biochemical matrix of normal skin tissue as chemical reaction environments. CuPC-based tattoo ink PB and both its blue and white pigment-enriched fractions demonstrate CAT and SOD-mimetic properties in vitro with effect sizes demonstrating a substantial dependence on the biochemical environment. PB constituents act as inhibitors of CAT but potentiate its activity in the biochemical matrix of the skin. CuPC-based BTI can mimic antioxidant enzymes, however chemical constituents other than CuPC (e.g. the photoreactive TiO2 ) seem to be at least partially responsible for the BTI redox-modulating properties.